2013
DOI: 10.1002/emmm.201202140
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of redox/Fyn/c‐Cbl pathway function by Cdc42 controls tumour initiation capacity and tamoxifen sensitivity in basal‐like breast cancer cells

Abstract: We found that basal-like breast cancer (BLBC) cells use Cdc42 to inhibit function of the redox/Fyn/c-Cbl (RFC) pathway, which normally functions to convert small increases in oxidative status into enhanced degradation of c-Cbl target proteins. Restoration of RFC pathway function by genetic or pharmacological Cdc42 inhibition enabled harnessing of pro-oxidant effects of low µM tamoxifen (TMX) concentrations – concentrations utilized in trials on multiple tumour types – to suppress division and induce death of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 52 publications
3
47
0
Order By: Relevance
“…In contrast, our studies demonstrate the importance of Cool-1 and its inhibition of c-Cbl in at least a subset of naturally occurring GBMs, one of the most deadly human cancers. Our studies also demonstrate Cdc42 and Cool-1 regulate c-Cbl function independently, such that Cdc42 knockdown had no effect in GBM cells and, conversely, Cool-1 knockdown had no effect on BLBC cells [3].…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…In contrast, our studies demonstrate the importance of Cool-1 and its inhibition of c-Cbl in at least a subset of naturally occurring GBMs, one of the most deadly human cancers. Our studies also demonstrate Cdc42 and Cool-1 regulate c-Cbl function independently, such that Cdc42 knockdown had no effect in GBM cells and, conversely, Cool-1 knockdown had no effect on BLBC cells [3].…”
Section: Discussionsupporting
confidence: 56%
“…Our studies emphasize the potential importance of c-Cbl inhibitors in tumor biology, by offering (together with our studies on BLBC cells [3]) the first demonstrations that such inhibition is critical in TIC function in human tumors and by raising the possibility that such inhibition is so critical to TIC function that two STEM CELLS different tumor types use distinct proteins to inhibit c-Cbl. Previous studies in lymphomas and other tumors demonstrated the importance of disruption of c-Cbl function as neoplastic stimuli, by direct mutation or by mutation of receptors to make them resistant to c-Cbl modulation (see, e.g., [28,29] for review).…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations